Iranians’ Identity throughout the History, the Emphasis on the Religious Identity - Rashid Rekabian; Morteza Babaee (تاریخ اسلام, 2022)
The identity considered as the necessity of survival and endurance of social life includes the elements such as the land, language, religion, government, ethnicity, traditions, intellectual inheritance, myths, and heroes. This research investigates the role of religion related to the development of Iranians’ identity throughout the history as well as the effect of religious identity of Iranians on the political and social alterations. Taking advantage of the descriptive and analytical method and library data, it is concluded that on the basis of evidences such as spirituality and theism, religion is considered as the inherent part of Iranian identity and it has an undeniable role in the events such as the advent of Tabaristan Alavis, Buyids, Safavid and the Islamic Revolution.